Impact of Safeguard Measures Import Duty Tax (BMTP) in Efforts to Increase Protection and Competitiveness of Textile Products : Dampak Pajak Bea Masuk Tindakan Pengamanan (BMTP) Dalam Upaya Meningkatkan Proteksi dan Daya Saing Produk Tekstil - Hidayatal Aliyah; Akhmad Mulyadi (Academia Open, 2024)
General background: The Safeguard Measures Import Duty Tax (BMTP) policy has been implemented to protect domestic industries from the adverse effects of rising imports. Specific background: In Indonesia, the textile industry has faced significant competition from imported goods, which threatens the competitiveness of local products. Knowledge gap: However, there is limited research on the effectiveness of the BMTP in enhancing protection and competitiveness, particularly in the context of the Juanda Customs and Excise Service Office. Aims: This study aims to evaluate the impact of BMTP on the protection and competitiveness of domestic textile products through qualitative methods, including observation, interviews, and documentation. Results: The findings reveal that the implementation of BMTP is effective in controlling and reducing the volume of imported textiles, thereby contributing to increased protection for domestic producers. Novelty: This research provides new insights into the specific application of BMTP at Juanda and highlights the use of Nvivo12 Plus software for qualitative analysis, offering a novel approach to triangulating data and ensuring validity. Implications: The results imply that BMTP can be a viable policy mechanism to safeguard domestic industries, particularly in sectors vulnerable to import surges, such as textiles, potentially informing future policy decisions to enhance industrial competitiveness. Highlights: BMTP effectively reduces textile imports, enhancing domestic protection. Nvivo12 Plus aids in qualitative data analysis for reliable results. The study offers insights into BMTP's specific application at Juanda Customs. Keywords: Import Duty Safeguard, Protection, Textile